ANALYSIS ON OSAKA DIALECTS VERBS AND NOUNS (STUDY OF STRUCTURE AND MEANING) - Natalia Desianti Tanzil; Utari Novella (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2020)
This research focuses on the structure and meaning of the sentence of Osaka Dialect and the standard Japanese itself. Osaka dialect is the most widely recognized on of Japanese dialect. An understanding or application of the Osaka dialect can be considered important so that when tourists, or who want to work or study in Osaka can understand the different structures and meanings that exist in standard Japanese and Osaka dialect, so as to avoid misunderstanding or miscommunication that is might happen. The method used in this research is descriptive analysis, which describes the structure and meaning on Osaka Dialects sentence. The data that were used in this research was obtained from a Japanese movie named 8UPPERS. Based on the data analysis, it can be concluded that Osaka Dialect tends to shorten and obliterate the sound from the verb of standard Japanese. For example, the sound in standard Japaneses word chigau shortens into chau in Osaka Dialect, meaning œwrong, œdifferent, and œisnt that right?. There were also changes on standard Japaneses sentence ending word such as ~nda and ~nanda, that turns into ~nen and ~yanen. Changes can also be seen on standard Japaneses past form of sentence ending word, ~tanda or ~ta to ~ten in Osaka Dialect. The ~naide form changes to ~ntoite in Osaka Dialect. The sound in present form of sentence ending word such as ~teiru also change to ~toru. There were also differences between the ~n and ~hen form that equals to ~nai form and the n form which came from ru. Change of sound can also be found on the ~shimatta form, which turns into ~shimota in Osaka Dialect.